Explicație pas cu pas:
a)
[tex](- 9)^{73} \div {3}^{144} - {16}^{12} \div {4}^{23} = - 9^{73} \div {3}^{2 \times 72} - {( {4}^{2} )}^{12} \div {4}^{23} = - 9^{73} \div {9}^{72} - {4}^{24} \div {4}^{23} = - 9 - 4 = - 13[/tex]
b)
[tex]\left[ {( - 4)}^{2} - {( - 3)}^{77} \div {( - 3)}^{75} \right] \div 7 = ({4}^{2} - {3}^{2}) \div 7 = (16 - 9) \div 7 = 7 \div 7 = 1[/tex]
c)
[tex] {( {3}^{5} )}^{4} \div \left[ {3}^{5} \times ( - {3}^{3} )^{6} \div {( - {3}^{2}) }^{5}\right] = {3}^{20} \div \left[ {3}^{5} \times {3}^{18} \div( - {3}^{10})\right] = {3}^{20} \div \left[ {3}^{23} \div( - {3}^{10})\right] = {3}^{20} \div ( - {3}^{13}) = - {3}^{7} [/tex]